1998
DOI: 10.1016/s0370-2693(98)00510-3
|View full text |Cite
|
Sign up to set email alerts
|

Large lepton mixing in a coset-space family unification on E7/SU(5)×U(1)3

Abstract: We study a coset-space unification model for families based on E 7 /SU(5)×U(1) 3 . We find that qualitative structure of quark and lepton mass matrices in this model describes very well the observation. We stress, in particular, that the large mixing angle, sin 2 2θ νµντ ≃ 1, required for the atmospheric neutrino oscillation reported by the SuperKamiokande collaboration, is naturally obtained, which is a consequence of unparallel family structure in the present coset-space unifi-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
161
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(166 citation statements)
references
References 18 publications
3
161
1
Order By: Relevance
“…In the present models, these ratios are quite predictive since 2 The tan ␤ dependence of the branching ratios is approximately tan 2 ␤. 1,2,0).…”
Section: Case 2 ä1mentioning
confidence: 58%
“…In the present models, these ratios are quite predictive since 2 The tan ␤ dependence of the branching ratios is approximately tan 2 ␤. 1,2,0).…”
Section: Case 2 ä1mentioning
confidence: 58%
“…Here we see that z = 0 corresponds to an "anarchical" MNS matrix [18,19], whereas z = 1 corresponds to a "semi-anarchical" MNS matrix [20]. The minimalist approach is to add only two righthanded neutrinos.…”
Section: Froggatt-nielsen Frameworkmentioning
confidence: 92%
“…Thus it is the fact that the unification of SU(5) × U(1) into SO(10) occurs only in higher dimensions that allows the missing partner mechanism to be implemented. Recently it has been found that realistic and simple models of quark and lepton masses can be constructed using so-called "lopsided" mass matrices [22,23,24,25]. The essential feature of such models is that the mass matrices of the down quarks and charged leptons are highly asymmetric and that M L ∼ M T D .…”
Section: An So(10) Model In Five Dimensionsmentioning
confidence: 99%